The Lapierre circus magic lantern slides. Issue 3 (3rd July 2018) - Moore, Dick
ABSTRACT: Two of the most popular forms of entertainment from the mid-18 th century onward, in addition to legitimate theater, were the circus and magic lantern shows. It was only natural that they would become intertwined. During this time, as France, along with Britain, became leading centers for the circus, France also became famous, though the work of Auguste Lapierre, for the development of magic lanterns and slides that could be used by families and children in their own homes. While Lapierre presented slides across a wide range of interests from fairy tales to political satire, among his output were a limited number of slides whose images depicted circus performers and acts from the famous circus venues. This article presents the visual imagery of these slides, including relevant notations regarding the performances and performers. It provides a rare and exciting historical view of the early circus acts and the acrobats that for decades have influenced performances around the world.